NEED ANALYSIS OF BUSINESS ENGLISH FOR ECONOMIC EDUCATION UNDERGRADUATE STUDENTS - Laila Desnaranti; Febby Pratama Putra (Research and Development Journal of Education, 2023)
Learning English is necessary for a variety of goals, not just for language fluency in general but also for more specific purposes (English for Specific Purposes). Business English is becoming more and more crucial as businesses demand that their employees speak multiple languages. The purpose of this research is to identify undergraduate students’ needs for business English using need analysis. The method that used in this research is descriptive qualitative approach. The researcher use questionnaire to find the undergraduate students’ need, lack, and want. The research result based on the questionnaire which can be concluded that learning English is essential for the undergraduate students and their motivation in learning English is to be able to communicate in formal or non-formal situation at business environments. The researchers came to the conclusion that the undergraduate students must enhance their english speaking ability because this is also one of their lack based on the questionnaire's findings. The result of this research will be used to develop a new syllabus and textbook for business English.